EFFECT OF WORKING CAPITAL MANAGEMENT ON FIRM’S VALUE: EVIDENCE FROM LISTED PHARMACEUTICAL FIRMS IN NIGERIA - Muhammed BELLO; Adeyemi KAMARDEEN; Shakirat Opeyemi SALAWUDEEN (Malete Journal of Accounting and Finance)
Effective working capital management is crucial for the success and sustainability of listed pharmaceutical firms in Nigeria. The study examined the working capital management on firm’s value: evidence from listed pharmaceutical firms in Nigeria. The specific objectives are to determine the effect of average collection period (ACP), average payment period (APP), cash conversion cycle (CCC) and inventory conversion period (ICP) on value of listed manufacturing firms in Nigeria. This study adopted an ex-post facto research design. The population of this study consists of all listed pharmaceutical companies on the floor of the Nigeria Exchange Group as at 31st December, 2021. There are eleven (11) listed pharmaceutical companies in Nigeria. Due to unavailability of data five (5) companies are used for the sample size of this study. The data obtained were analyzed using descriptive techniques such as minimum, maximum, mean, and standard deviation and inferential techniques such as correlation and regression analysis. The study revealed that average collection period (ACP), average payment period (APP), cash conversion cycle (CCC) and inventory conversion period (ICP) have significant effect on value of listed manufacturing firms in Nigeria. The study conclude that the working capital management has significant effect on firm’s value of listed pharmaceutical firm. This study recommends regularly review and adjust working capital management strategies to ensure alignment with changing business needs and invest in financial technology and automation to streamline working capital management processes. It also recommends that implement efficient accounts receivable management to reduce average collection period and negotiate with suppliers to extend payment terms and reduce average payment period.